Pengaruh Marketing Mix dan Self Service Technology Terhadap Keputusan Nasabah Memilih Tabungan Hijrah Bank Muamalat - Sulfia, Sulfia; Nuraeni Gani; Trimulato, Trimulato (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
This research aims to determine the effect of Marketing Mix and Self-service technology on customer decisions in conducting transactions at the Makassar branch of Bank Muamalat. This research method is quantitative by describing the influence of marketing mix and self-service technology on customer decisions. This type of research is a field study, primary data collection. Source of research data obtained from quisioner. The data analysis technique used is descriptive quantitative. The research results obtained from the marketing mix t test have a significant effect on customer decisions with a tcount > ttable (2.00665) of 3,786 and a significant value of 0.000, this probability value is below 0.05. Meanwhile the t test shows the results that self-service technology has a significant effect on customer decisions with a tcount > ttable (2.00665) of 4.130, a significant value of 0.000 and a probability value below 0.05. The effect of marketing mix and self-service technology on customer decisions is that the Fcount value is greater than the Ftable value, namely 44,752 > 3.18 with a significant value of 0.000 less than 0.05 (0.000 <0.05), then H0 is rejected and H3 is accepted, meaning that marketing mix and self-service technology variables simultaneously have a significant effect on customer decisions in using Bank Muamalat Makassar branch hijrah savings.